2013
DOI: 10.2215/cjn.00710113
|View full text |Cite
|
Sign up to set email alerts
|

World Incidence of AKI

Abstract: SummaryBackground and objectives The burden of AKI around the globe has not been systematically examined.Design, setting, participants, & measurements A systematic review (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) of large cohort studies was conducted to estimate the world incidence of AKI and its stages of severity and associated mortality, and to describe geographic variations according to countries, regions, and their economies. AKI definitions were reclassified according to the Kidney Disease I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
837
14
26

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,207 publications
(955 citation statements)
references
References 19 publications
28
837
14
26
Order By: Relevance
“…As a pathologic response, the anemia directly reduces the delivery of oxygen. Because AKI frequently develops in the ischemic conditions, anemia can be one of reasons for the high incidence of AKI in hospital-admitted patients (i.e., 1 in 5 adults and 1 in 3 children patients) (Susantitaphong et al 2013). Previous studies in several clinical settings (Karkouti et al 2009;Legrand et al 2013;Sickeler et al 2014) and our ICU results support the relationship between anemia and AKI.…”
Section: Discussionsupporting
confidence: 79%
“…As a pathologic response, the anemia directly reduces the delivery of oxygen. Because AKI frequently develops in the ischemic conditions, anemia can be one of reasons for the high incidence of AKI in hospital-admitted patients (i.e., 1 in 5 adults and 1 in 3 children patients) (Susantitaphong et al 2013). Previous studies in several clinical settings (Karkouti et al 2009;Legrand et al 2013;Sickeler et al 2014) and our ICU results support the relationship between anemia and AKI.…”
Section: Discussionsupporting
confidence: 79%
“…None of the centers was in a low-income country, only 8.9 % of the patients came from lower-middle-income countries, and only 5.9 % were treated in countries where less than 5 % of the GDP is spent on health care. These results are in line with a recent systematic review evaluating the world incidence of AKI [2]. In this systematic review, among the 3.6 million patients evaluated in 154 studies, the vast majority of the studies (130; 84.4 %) accounting for 3.3 million patients came from high-income countries and only two studies (2227 patients) originated from low-or low-middle-income countries [2].…”
supporting
confidence: 86%
“…In this systematic review, among the 3.6 million patients evaluated in 154 studies, the vast majority of the studies (130; 84.4 %) accounting for 3.3 million patients came from high-income countries and only two studies (2227 patients) originated from low-or low-middle-income countries [2]. Unlike Hoste et al, this study found mortality to be inversely correlated with proportion of GDP spent at health care and with the country gross national income per capita [2]. This discrepancy may have several explanations.…”
mentioning
confidence: 99%
“…Acute kidney injury (AKI) occurs frequently during hospitalization [1] and is associated with deleterious effects [2,3]. The need for renal replacement therapy (RRT) in AKI is rising [4] and continuous RRT (CRRT), extended daily dialysis (EDD) and intermittent hemodialysis (IHD) are the most commonly used techniques in developed countries.…”
Section: Extended Daily Dialysis Versus Intermittent Hemodialysis Formentioning
confidence: 99%